Perempuan dalam Kaba: Telaah dari Perspektif Semiotika Roland Barthers - Denni Dwi Putriyanti; Ernida Kadir; Hardi Hardi (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
This article aims to find out the meaningful indications contained in the Perempuan Dalam Kaba dance work and the differences in the dynamics of male and female dancers' movements and the denotation and connotation forms of the Perempuan Dalam Kaba dance from Roland Barthers' semiotic perspective. In this case, qualitative and descriptive analysis methods are used to discuss the denotation and connotation forms in the Perempuan Dalam Kaba dance work and the choreography contained in Perempuan Dalam Kaba. In writing this thesis, the theory of Choreography is used, and the theory of Roland Barthers from these two theories has a role in each discussion in this paper.